Acupuncture alleviates chronic pain and comorbid conditions in a mouse model of neuropathic pain: the involvement of DNA methylation in the prefrontal cortex. Issue 2 (February 2021) - Jang, Jae-Hwan; Song, Eun-Mo; Do, Young-Ho; Ahn, Sora; Oh, Ju-Young; Hwang, Tae-Yeon; Ryu, Yeonhee; Jeon, Songhee; Song, Mi-Yeon; Park, Hi-Joon
Abstract : Abstract: Chronic pain reduces life quality and is an important clinical problem associated with emotional and cognitive dysfunction. Epigenetic regulation of DNA methylation is involved in the induction of abnormal behaviors and pathological gene expression. We examined whether acupuncture can restore epigenetic changes caused by chronic pain, and identified the underlying mechanisms in neuropathic pain mice. Acupuncture treatment for 6 months (3 days/week) improved mechanical/cold allodynia and the emotional/cognitive dysfunction caused by left partial sciatic nerve ligation (PSNL)-induced neuropathic pain. The effects of acupuncture were associated with global DNA methylation recovery in the prefrontal cortex (PFC). Analysis of DNA methylation patterns in PFC indicated that 1364 overlapping genes among 4442 and 4416 methylated genes in the PSNL vs sham and PSNL vs acupuncture points groups, respectively, were highly associated with the DNA methylation process. Acupuncture restored the reduced expression of 5-methylcytosine, methyl-cytosine-phospho-guanine binding protein 2, and DNA methyltransferase family enzymes induced by PSNL in PFC. Methylation levels of Nr4a1 and Chkb associated with mitochondrial dysfunction were decreased in PFC of the PSNL mice, and increased by acupuncture. By contrast, high expression of Nr4a1 and Chkb mRNA in PSNL mice decreased after acupuncture. We also found that acupuncture inhibited the expression of Ras pathway-related genes such as Rasgrp1 and Rassf1 . Finally, the expression of Nr4a1, Rasgrp1, Rassf1, and Chkb mRNA increased in the neuronal cells treated with Mecp2 small interfering RNA. These results suggest that acupuncture can relieve chronic pain-induced comorbid conditions by altering DNA methylation of Nr4a1, Rasgrp1, Rassf1, and Chkb in the PFC. Abstract : Supplemental Digital Content is Available in the Text.Acupuncture treatment for 6-month period altered DNA methylation patterns, particularly in the prefrontal cortex, in a mouse model of chronic neuropathic pain.